The Application of Behaviorism Theory Through Scout Extracurriculars in Forming Elementary School Student Discipline - Yuliana Yuliana; Eva Imania Eliasa (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study examines how behaviorist tactics, particularly classical conditioning, in scout extracurricular activities affect student conduct in a Palembang primary school. From April to May 2023, this qualitative study included observation data, interviews, and documentation. Students in grades 5 and 6 were selected for the study because they were more mature and had extensive learning experiences. Wider than poorer pupils. This is essential because behaviorist theory is seen to shape student character more at this time. Student scout extracurricular engagement is the topic of this study. Behavioralism-aligned activities that emphasize personal growth and service were selected. Careful information gathering, inference, presentation, and verification are done in this study. Final findings are analyzed using different methods. The study shows that extracurricular activities, particularly scouting, help improve primary school children's impulse control. These results may assist educators, mentors, and extracurricular coaches teach their kids character and self-control for success in and out of school. This study may also inform classroom behaviorism research.